Preventive effect of Coriandrum sativum on neuronal damages in pentylentetrazole-induced seizure in rats - Mojtaba Pourzaki; Mansour Homayoun; Saeed Sadeghi; Masoumeh seghatoleslam; Mahmoud Hosseini; Alireza Ebrahimzadeh Bideskan (Mashhad University of Medical Sciences, 2017)
Objective:Coriandrum sativum (C. sativum) as a medicinal plant has been pointed to have analgesic, hypnotic and anti-oxidant effects. In the current study, a possible preventive effect of the hydro-alcoholic extract of the plant on neuronal damages was examined in pentylenetetrazole (PTZ) rat model of seizure.Materials and Methods: Forty male rats were divided into five main groups and treated by (1) saline, (2) PTZ: 100 mg/kg PTZ (i.p) and (3-5) 50, 100 and 200 mg/kg of hydro-alcoholic extract of C. sativum during seven consecutive days before PTZ injection. After electrocorticography (ECoG), the brains were removed to use for histological examination.Results:  All doses of the extract reduced duration, frequency and amplitude of the burst discharges while prolonged the latency of the seizure attacks (p